TWO NEW FLATFISHES FROM THE INDO-AUSTRALIAN ARCHIPELAGO, WITH A SYNOPSIS OF THE SPECIES OF THE GENERA POECILOPSETTA AND NEMATOPS. - NORMAN, J R (Research Center for Biology, 1931)
abstract not available